Vernacular literature in eighth- and ninth-century Mercia - Wragg, S (2017)
This dissertation reads a group of Old English prose and verse texts that linguistic evidence suggests probably originated in Mercia, within the context of eighth- and ninth-century Mercian cultural and political history. This approach complements and supplements existing scholarship, offering evidence that the theory that a culture of vernacular translation and composition thrived in Mercia has fruitful explanatory powers. It articulates a theoretical narrative of the early period of Old English literature, and identifies two major trends that can be linked to the political and material culture of Mercia in the eighth and ninth centuries. The first is the proliferation of vernacular hagiography, both in prose and verse. In the first chapter, I offer an overview of Anglo-Saxon texts connected with the cult of Guthlac, a saint closely connected to the Mercian dynasty in the eighth and ninth centuries. This chapter offers an interpretation of Felix's Vita sancti Guthlaci as an iteration of Mercian identity, and highlights the way in which Guthlac A asserts and emphasizes the saint’s Mercian identity. I then propose a revival of the cult of Guthlac linked to a crisis in the Mercian succession in the ninth century, to which the possibly Cynewulfian account of Guthlac's death in Guthlac B, the Old English prose translation of Felix's life, and the entries in the Old English Martyrology, may be connected. In Chapter 2, I offer a reading of the hagiographical poetry of Cynewulf, namely Juliana and Elene, in light of the remarkably – and arguably uniquely – powerful position of women in Mercia from the reign of Offa onwards. The early cult of Juliana appears to have a Mercian bias, and the empowered female saints in Cynewulf's works may also be connected to evidence for female literacy in the Tiberius-group manuscripts, all of which originate in eighth- and ninth-century Southumbria. In Chapter 3, I read the Old English translation of Bede's Historia ecclesiastica, a major though until recently little-studied prose work, in relation to other texts with a literal style of translation and a hagiographical focus, and its apparent interest in Mercian conciliar culture. I also propose that the style of illumination of the earliest extant copies of the Old English Historia ecclesiastica may be influenced by Mercian, Tiberius style. The second major trend which the material and literary culture of Mercia manifests in this period is an early Orientalism, imitating and appropriating Eastern models as signs of power and sophistication. Sculptures such as those at Breedon-on-the-Hill, Leicestershire, in which Mary is modelled on Byzantine sculpture, or the dinar of Caliph al-Mansur (773-4), reminted as coinage for Offa, demonstrate a deep engagement with Oriental culture prevalent in Mercia during this period. Several decorative elements in the eighth- and ninth-century Tiberius group manuscripts, which have stylistic affinities and are often associated with Mercia, also have Oriental origins. This same phenomenon is traceable in the literary record. For example, Cynewulf's works engage in various ways with different regions of the Orient, including the Mediterranean, Africa, Rome, Jerusalem and India. The Old English Martyrology combines Insular and continental saints with Eastern saints. The Oriental character of two of the prose texts of BL Cotton Vitellius A. xv., The Letter of Alexander to Aristotle and The Wonders of the East, both usually considered Mercian on linguistic grounds, has been long noted. Together with its manuscript neighbours, Wonders and Beowulf, I consider the Letter's interest in the wider world, as well as its theorization of kingship, by which it might be considered a speculum regum. This thesis reads these texts in the light of various forms of evidence for Mercian literary culture, including linguistic characteristics and preexisting scholarship. In so doing, it fleshes out a theoretical narrative of vernacular literature prior to the late ninth-century Alfredian renaissance.